Australian foreign policy in the age of terror - Ungerer, Carl (UNSW Press, 2008)
Examines changes to Australian foreign policy since 9/11 and the rise of global Islamic terrorism. This title covers each of the main areas of Australian foreign policy security, trade, development assistance, multilateral institutions and bilateral relations. It deals with the strategic dimensions of foreign policy